PRECIPITATION, EVAPORATION AND ENERGY EXCHANGE AT THE SURFACE OF THE SOUTHEAST ASIAN WATERS - Wyrtki, Klaus (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1957)
None provided.